THINKING SYSTEMS IN THE FRAMEWORK OF VALUE - Rasyid Anwar Dalimunthe (Journal Analytica Islamica, 2021)
Systemic thinking is a way of thinking that looks at events in order from the simplest to the most complex. Examples of systemic thinking, for example, recognize the process of human formation starting from the womb, birth, childhood, becoming an adult, until death. While looking at human development itself is influenced by various factors, such as the social environment, family, and the food eaten; all are examples of systems thinking. The method used to obtain the data needed in this discussion is the Library Research method. The result is that ethical values are intended for humans only, other than humans (animals, objects, nature) do not contain ethical values, therefore it is impossible to be punished for good or bad, wrong or right. While aesthetics is more inclined to beauty and art that is seen by the eye. The schools in value are materialism, hedonism, utilitarianism, intuition, evolution and naturalism. From some of these schools there are similarities in looking at the good and bad of a life, but this school also has different views about the good and bad of a life. But in Islamic teachings to say his life is good or bad it can be seen from the revelations of Allah SWT listed in the holy book of the Qur'an.